Drivers of the variability of soil phosphorus fractions in boreal forested watersheds - Nora J. Casson; Chammi P. Attanayake; Geethani Amarawansha; Mauli Gamhewage; Darshani Kumaragamage; Jeremy G. Leathers; U.W.A. Vitharana (FACETS, 2025)
In the boreal forest, phosphorus (P) is tightly cycled and can be heterogenous in its distribution across the landscape. Characterizing chemical, physical, and landscape-scale drivers of variability in both concentration and forms of soil P can help us understand how P dynamics will respond to environmental change; however, data on forms of soil P in boreal forests are sparse. The goal of this study was to assess the variability of soil P across a boreal forested watershed. Seventy-four surface soil samples from a boreal forested catchment were analyzed for a suite of chemical and physical characteristics, and were paired with geospatial data to develop predictive models of forms of soil P. Water-extractable P concentrations were low, while total P (65.7–2197 mg kg−1) and plant-available (Mehlich-3-extractable) P (0.63–193 mg kg−1) concentrations varied widely across the study area. Partial least squares regression results indicated that plant-available P was strongly related to soil Mn and Ca content, while total P was more strongly related to organic C and wetness index. These results suggest that soil P can vary widely, even in nutrient-poor boreal ecosystems, and site-specific characteristics may play an important role in predicting variability.